Tendência sócio-cultural da alimentação saudável no Brasil e sua re-significação a partir da publicidade: um estudo de caso da campanha Maxi-goiabinha da Bauduco - Bedendo, Marcos Henrique (2010)
Sociocultural tendencies are usually incorporated in the consumer goods markets thru products and advertising campaigns. In order to achieve that, the industry tends to re - signify the tendencies to transform them into sales arguments for its new products. This study takes as object a product launched in the marketplace, the Maxi-Goabinha from Bauducco brand, and discusses thru bibliographical references and market examples how this product is re-signified. This study objective it to identify in which way the healthy eating tendency was simplified and transformed into icons and lifestyles by the advertising of the product Maxi-Goiabinha. The study searches for elements that became influences for the campaign, the reason for these elements to be used and what were the potential impacts of the product in its marketplace. The product Maxi-Goiabinha was chosen because it belongs to a well known indulgent brand, Bauducco, and it tries to fit in a healthy market that is not part of the original brand positioning. This relation shows how fragile the brand is to keep its integrity when challenged with the opportunity to increase its incomes by exploring a market trend. The conclusions shows that advertising provides consumers with information, and with that, they tend to search for healthier characteristics in the consumer market, causing a positive change in the products offered by industry. However, by using as icons characters that are able to achieve a perfect balance between heath, professional and personal life, an increase in anxiety may be generated in the average consumer to become as successful as this ideal man or woman. It is discussed if the choices offered by the industry in the contemporary consumption environment oppress or freed the consumer, since at the same time that the power of choice is given to them, advertising pressure the consumers to be as happy and successful as its own characters in the many aspects of life that accompanies the multiplicity of the contemporary living.